Nox emissions from diesel cars increase with altitude. (February 2023) - Chen, Yuche; Wu, Xuanke; Hu, Kejia; Borken-Kleefeld, Jens
Highlights: Conduct remote sensing emission measurements of vehicles at different altitudes. Analyze NOx emission rate from diesel cars by controlling vehicle and meteorology features. Find significant higher NOx emission rates as altitude increases by controlling all features. Discuss possible reasons and policy implications in transportation emission inventories. Abstract: NOx emissions from diesel cars and light duty vehicles are important to regulate because of their significant health and environmental damages. Many factors can influence vehicle-related NOx emissions, but limited studies have explored NOx emissions as a function of altitude. In this study, we report on the NOx emission rate from diesel cars when driven in altitudes of about 1, 500 m above sea level. Specifically, we analyze data from remote emission-sensing campaigns at three locations and altitudes in Switzerland (Davos, Zurich, and Basel). We control factors such as emission standard, engine load, ambient temperature, humidity, and manufacturer to investigate relationship between NOx emission and altitude. We find the NOx emission rate increases by a factor two or more as measured at Davos, about 1, 500 m above sea level, compared with the other two low-altitude locations. We discuss potential policy implications and recommend including this effect in emission factor models and traffic emission inventories.